CeO2 coated NaFeO2 proton-conducting electrolyte for solid oxide fuel cell. (26th February 2021) - Xing, Yueming; Akbar, Muhammad; Yousaf, Muhammad; Shah, MAK Yousaf; Xia, Chen; Gao, Jie; Wang, Xunying
Abstract: Nowadays, the low-temperature operation has become an inevitable trend for the development of SOFCs. Transition metal layered oxides are considered as promising electrolyte materials for low-temperature solid oxide fuel cells (LT-SOFCs). In this work, we report the CeO2 coated NaFeO2 as an electrolyte material for LT-SOFC. The study results revealed that the piling of CeO2 significantly influenced the open-circuit voltage (OCV) as well as the power output of the fuel cells. In comparison with pure NaFeO2, the denser structure of CeO2 coated NaFeO2 leads to higher OCV (1.06 V, 550 °C). The electrochemical impedance spectrum (EIS) fitted results showed that NaFeO2 –CeO2 composites possessed higher ionic boundary conductivity. This is because that the hetero-interfaces between NaFeO2 and CeO2 provide fast ion conducting path. The high ionic conductivity of CeO2 coated NaFeO2 lead to admirable fuel cell power output of 727 mW cm −2 at 550 °C. Highlights: Core cell NaFeO2 –CeO2 composites act as electrolyte of LT-SOFC. At 550 °C, the OCV is 1.06 V; Pmax is 727 mW cm −2 . Power output of NaFeO2 @CeO2 based FC improved with CeO2 content increasing. NaFeO2 @CeO2 shows higher ionic grain boundary conductivity than NaFeO2 .